Handbook of research on artificial intelligence, innovation and entrepreneurship - Carayannis, Elias G.; Grigoroudis, Evangelos (Research handbooks in business and management series, 2023)
"The Handbook of Research on Artificial Intelligence, Innovation and Entrepreneurship focuses on theories, policies, practices, and politics of technology innovation and entrepreneurship based on Artificial Intelligence (AI). It examines when, where, how, and why AI triggers, catalyzes, and accelerates the development, exploration, exploitation, and invention feeding into entrepreneurial actions that result in innovation success. Individual chapters explore the factors that shape and drive innovation and entrepreneurship, including modalities (such as the Internet of Things (IoT)), challenges (such as privacy and safety concerns), and opportunities (such as augmenting the efficacy frontier of technological solutions enabled by AI). This Handbook provides comprehensive coverage of AI, technology, and innovation and entrepreneurship for academics, policy makers, practitioners, and students"--